Comparison of the effective orifice area of prosthetic mitral valves using two-dimensional versus three-dimensional transesophageal echocardiography - Zhou, Lei (J Int Med Res, 2021)
OBJECTIVE: This study compared the continuity equation-based effective orifice area (EOA) of prosthetic mitral valves between two-dimensional (2D) and 3D transesophageal echocardiography (TEE). METHODS: Thirty-four patients without major aortic valve abnormalities underwent mitral valve replacement surgery. The EOAs of prosthetic mitral valves were calculated using the continuity equation with 2D and 3D TEE. For 18/34 patients using a biological valve prosthesis, the EOA of the prosthesis was obtained from commercial records. RESULTS: The EOA of prosthetic mitral valves significantly varied between the 2D and 3D methods (2.22 ± 0.71 vs 2.35 ± 0.70 cm(2), n = 34). The area of the diameter of the left ventricular outflow tract as determined by the 3D method was significantly higher than that by the 2D method (mean difference: −0.14 ± 0.20 cm(2)), with 95% coherence boundaries of −0.53 and 0.25 cm(2). The regression equation for the EOA by 3D and 2D TEE was y = 0.27 + 0.94x, with a good correlation. CONCLUSIONS: The EOA of prosthetic mitral valves is underestimated using the 2D TEE method compared with the 3D TEE method. The 3D-TEE method has the advantage of higher precision over the 2D TEE method, and it may be helpful for better assessment of prosthetic mitral valves intraoperatively.